Garlic prevents the oxidizing and inflammatory effects of sepsis induced by bacterial lipopolysaccharide at the systemic and aortic level in the rat. Role of trpv1 - Juan Carlos Torres-Narváez; Israel Pérez-Torres; Leonardo del Valle-Mondragón; Vicente Castrejón-Tellez; Verónica Guarner-Lans; María Sánchez-Aguilar; Elvira Varela-López; Álvaro Vargas-González; Gustavo Pastelín-Hernández; Julieta Anabell Díaz-Juárez (Heliyon, 2023)
Garlic (Allium sativum) possesses healing properties for diseases like systemic arterial hypertension, cancer and diabetes, among others. Its main component, allicin, binds to the Transient Receptor Potential Vanilloid Type 1 (TRPV1). In this study, we investigated TRPV1′s involvement in the regulation of various molecules at the systemic and aortic levels in Wistar rats treated with bacterial lipopolysaccharide (LPS) and garlic to activate the receptor. The experimental groups were as follows: 1) Control, 2) LPS, 3) Garlic, and 4) LPS + Garlic.Using Uv–visible spectrophotometry and capillary zone electrophoresis, we measured the levels of nitric oxide (NO), biopterins BH2 and BH4, total antioxidant capacity (TAC) and oxidizing capacity (OXCA). We also analyzed molecules related to vascular homeostasis such as angiotensin Ang 1–7 and Ang II, as well as endothelin ET-1. In addition, we assessed the inflammatory response by determining the levels of interleukin-6 (IL-6), tumor necrosis factor alpha (TNFα), and galectin-3 (GTN-3). For cell damage assessment, we measured levels of malondialdehyde (MDA), malonate (MTO) and 8-hydroxy-2-deoxyguanosine (8HO2dG).The results showed that LPS influenced the NO pathway at both systemic and aortic levels by increasing OXCA and reducing TAC. It also disrupted vascular homeostasis by increasing Ang-II and ET-1, while decreasing Ang1-7 levels. IL-6, TNFα, GTN-3, as well as MDA, MTO, and 8HO2dG were significantly elevated compared to the control group. The expression of iNOS was increased, but TRPV1 remained unaffected by LPS. However, garlic treatment effectively mitigated the effects of LPS and significantly increased TRPV1 expression.Furthermore, LPS caused a significant decrease in calcitonin gene-related peptide (CGRP) in the aorta, which was counteracted by garlic treatment. Overall, TRPV1 appears to play a crucial role in regulating oxidative stress and the molecules involved in damage and inflammation induced by LPS. Thus, studying TRPV1, CGRP, and allicin may offer a potential strategy for mitigating inflammatory and oxidative stress in sepsis.